2024
DOI: 10.3390/buildings14020396
|View full text |Cite
|
Sign up to set email alerts
|

Towards Designing Durable Sculptural Elements: Ensemble Learning in Predicting Compressive Strength of Fiber-Reinforced Nano-Silica Modified Concrete

Ranran Wang,
Jun Zhang,
Yijun Lu
et al.

Abstract: Fiber-reinforced nano-silica concrete (FrRNSC) was applied to a concrete sculpture to address the issue of brittle fracture, and the primary objective of this study was to explore the potential of hybridizing the Grey Wolf Optimizer (GWO) with four robust and intelligent ensemble learning techniques, namely XGBoost, LightGBM, AdaBoost, and CatBoost, to anticipate the compressive strength of fiber-reinforced nano-silica concrete (FrRNSC) for sculptural elements. The optimization of hyperparameters for these tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 127 publications
0
5
0
Order By: Relevance
“…As depicted in Figure 1, a correlation factor of "1" is observed for the same parameters. When one parameter changes, the other parameter also changes [24,25]. As can be seen from Figure 1, the overall correlation is below 0.3, which means that the selected input parameters are not highly correlated and can be effectively used in the learning and prediction of machine learning models.…”
Section: Methodsmentioning
confidence: 99%
“…As depicted in Figure 1, a correlation factor of "1" is observed for the same parameters. When one parameter changes, the other parameter also changes [24,25]. As can be seen from Figure 1, the overall correlation is below 0.3, which means that the selected input parameters are not highly correlated and can be effectively used in the learning and prediction of machine learning models.…”
Section: Methodsmentioning
confidence: 99%
“…A population-based metaheuristic approach called particle swarm optimization iteratively proceeds to discover the best individual particle by optimizing a problem. In actuality, it is appropriate for very large-scale problems and makes very few assumptions about the current problem [118][119][120]. Positions are updated during PSO construction when better positions are discovered using a specific merit function.…”
Section: Particle Swarm Optimization (Pso)mentioning
confidence: 99%
“…To understand the predictive results of the clogging behavior with other research and standard codes, an in-depth comparison was conducted with the previous studies [65,66]. Figure 12 demonstrates the comparison between the proposed model and the previous studies (one is a physical-based prediction model considering the clogging behavior [67,68]; the other is a hybrid machine learning algorithm based on a PSO-SVM model [52]). It can be observed that the prediction results based on the machine learning models are better than the physical model.…”
Section: Evaluation Of the Modelmentioning
confidence: 99%
“…This is because the proposed physical models are more based on idealized assumptions. For example, the connected pore is assumed to be an equally thick permeable pipe [67,68], or the porosity of the concrete specimens is assumed to be consistent in different sections [67,68]. It is easy for the physical model to be inconsistent with the actual seepage when predicting the permeation decay behavior of pervious concrete, which leads to the low prediction reliability of the physical model.…”
Section: Evaluation Of the Modelmentioning
confidence: 99%